The Effect of Reproductive Health Counseling on the Level of Knowledge About Premarital Sex - Ardiana Batubara (Golden Ratio of Data in Summary, 2024)
This study investigates the impact of reproductive health counseling on adolescents' knowledge regarding premarital sex. Reproductive health counseling serves as an educational tool to improve adolescents' understanding of reproductive health issues, aiming to reduce the prevalence of risky sexual behaviors and the negative consequences associated with premarital sex, such as sexually transmitted infections (STIs) and unintended pregnancies. A pre-experimental design was employed, utilizing a one-group pretest-posttest approach. The sample consisted of 81 adolescents selected from a population of 433 students at MAN 2 Deli Serdang in 2023. Data was collected through direct engagement with participants, who completed a structured questionnaire to assess their knowledge before and after the counseling sessions. The findings indicate a significant improvement in adolescents' knowledge levels after receiving reproductive health counseling. The analysis, conducted using a paired sample T-test via SPSS, resulted in a p-value of 0.000, indicating a statistically significant difference between pre-counseling and post-counseling knowledge levels (p < 0.05). This suggests that reproductive health counseling effectively increased the adolescents' knowledge about premarital sex. The study concludes that reproductive health counseling positively impacts the level of knowledge regarding premarital sex among adolescents at MAN 2 Deli Serdang. It is recommended that school authorities collaborate with healthcare centers to facilitate regular educational sessions, ensuring that adolescents are well-informed about reproductive health and the risks associated with premarital sexual activities.